2009
DOI: 10.1161/strokeaha.108.545574
|View full text |Cite
|
Sign up to set email alerts
|

Dispatcher Recognition of Stroke Using the National Academy Medical Priority Dispatch System

Abstract: Background and Purpose— Emergency medical dispatchers play an important role in optimizing stroke care if they are able to accurately identify calls regarding acute cerebrovascular disease. This study was undertaken to assess the diagnostic accuracy of the current national protocol guiding dispatcher questioning of 911 callers to identify stroke (QA Guide version 11.1 of the National Academy Medical Priority Dispatch System). Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 23 publications
(18 reference statements)
1
69
2
3
Order By: Relevance
“…[7][8][9] If this is to be increased, it is necessary to identify those symptoms likely to have a high sensitivity in relation to a final diagnosis of stroke. The characteristics with the highest sensitivities were having no to only slight pre-stroke disability, and being alert.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] If this is to be increased, it is necessary to identify those symptoms likely to have a high sensitivity in relation to a final diagnosis of stroke. The characteristics with the highest sensitivities were having no to only slight pre-stroke disability, and being alert.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, delays in presentation and specialist assessment frequently prevent patients from receiving rtPA. Emergency medical dispatch sensitivity and positive predictive value (PPV) for identifying stroke is < 50%, [7][8][9] and this is compounded by long delays in patients accessing emergency medical services (EMSs). 10 Studies have shown that activation of the EMSs is the single most important factor in the rapid triage and treatment of acute stroke patients.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambulance crews successfully priority transport remained at only a small fraction below 90% (Table 15). , Buck et al 2009, Krebes et al 2012, Jones et al 2013) and prehospital stroke care. However, even for these eventually recanalized patients there still remains some room for improvement as the assignment of calls to high priority and stroke code status in dispatch and transportation did not reach 100%.…”
Section: Stroke Recognition By the Emds And Ambulance Crews (Iii)mentioning
confidence: 99%
“…Some studies are done in this regard, indicating that operators did not diagnose serious medical problems. One of the aims of medical emergency systems is making a balance between available resources to provide for the patients and the amount of patients' need to them (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%